Pembelajaran Pendidikan Agama Islam Berbasis Multikultural Humanistik dalam Membentuk Budaya Toleransi Peserta Didik Di SMA Negeri Model Madani Palu, Sulawesi Tengah - Hamlan Andi Baso Malla (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This research aims to determine the development of humanistic multicultural education in learning Islamic religious education, and implementation of Islamic religious education in a culture of tolerance in SMA Negeri Model Madani Palu. This research uses qualitative method through purposive sampling technique approach. The result of this research showed that the development of humanistic multicultural values in the learning of Islamic education is carried out according to the objectives, materials, methods and evaluation of learning in the syllabus and RPP 3 (three) hours a week. Extracurricular activities held every Saturday as an additional lesson of Islamic religious education and manners through the school program “Bina Imtaq”. Culture of tolerance implemented through the learning of Islamic education and character through the attitude and exemplary teachers of Islamic education and teachers of other subjects